63.0k views
0 votes
Question20................

Question20................-example-1
User Polmarex
by
6.7k points

1 Answer

3 votes

Answer: 1/b^2 or b^-2

By Laws of exponents we have the relationship of;

If m>n

a^m/a^n = a^m-n

If m<n

a^m/a^n = 1/a^n-m

And;

a^-n = 1/a^n

Also we have;

(a^m)*(a^n) = a^m+n

So let’s look at our problem;

b^-6/b^-4 = b^-6-(-4) = b^-2 = 1/b^2

Or we can do it this way;

b^-6/b^-4= (b^-6)*(b^4)= b^-6+4= b^-2= 1/b^2

If you have any questions please feel free to ask. Thanks and have a blessed day!

User Dreagen
by
5.1k points